The Effect of the PjBL Model with Interactive Maps on History Learning Outcome of Students at SMK 3 Pontianak: Pengaruh Model PjBL dengan Peta Interaktif terhadap Hasil Belajar Sejarah Siswa SMK 3 Pontianak - LEONY ARTANEVIA; astrini eka putri; Andang Firmansyah (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
History learning in vocational high schools often suffers from low student engagement due to the traditional teaching methods. This study examined the effect of Project-Based Learning (PjBL) model supported by interactive maps on Grade X students history learning outcomes at SMK Negeri 3 Pontianak. A quasi-experimental design was used, with an experimental class taught using PjBL and interactive maps and a control class taught conventionally. Data were collected through cognitive tests and psychomotor assessments and analyzed using the Mann-Whitney U test dan effect size calculations. The results showed significant differences between classes (p < 0,000), with the experimental class achieving higher cognitive (89,18 vs. 71,63) and psychomotor scores (85,45 vs. 57,73). Effect size for cognitive (r = 0,78) and psychomotor outcomes (r = 0,855) indicate a strong influence. The novelty of this study lies in the combination of PjBL with interactive maps, supported by a relatively large sample size and rigorous analysis of both cognitive and psychomotor learning outcome.